Nursing students' experiences with clinical placement in residential aged care facilities: a systematic review of qualitative evidence. Issue 5 (May 2020) - Keeping-Burke, Lisa; McCloskey, Rose; Donovan, Cindy; Yetman, Linda; Goudreau, Alex
ABSTRACT: Objective: The objective of this systematic review was to synthesize the best available evidence on nursing students' experiences with clinical placement in residential aged care facilities. Introduction: Nursing education programs play a key role in preparing future nurses to care for the growing number of older adults who will require health care. A key component of this preparation involves ensuring that curricula optimize student learning through carefully designed clinical learning practice experiences. Residential aged care facilities provide students with opportunities to work exclusively with older adults. Studies that address clinical placements in residential aged care facilities highlight both the benefits and concerns of student learning and professional development. Insight into student experiences of clinical placements in residential aged care facilities can help inform nursing curricula and contribute to a better understanding of how best to prepare students to care for an aging population. Inclusion criteria: This review considered all qualitative studies that included undergraduate and diploma nursing students. Nursing students included individuals or groups identified as nursing students independent of the type of program, level of learning, or time spent in the setting. Methods: A three-step search strategy was used to identify English language qualitative primary research studies. Two reviewers independently appraised the included studies using the JBI Critical Appraisal Checklist for Qualitative Research. Key findings were extracted and classified as unequivocal or credible. Results: Fourteen qualitative studies were included, published between 2003 and 2018. A total of 53 findings were extracted and aggregated into seven categories. From the seven categories, two synthesized findings were developed: the evolution of learning and embracing opportunity. Conclusion: This review captured student experiences of clinical placement in residential aged care facilities. The findings highlight the importance of students entering the setting with knowledge of how to care for older adults and being able to respond to challenging resident behavior. Equally important is the need for students to understand the roles and contributions of all care staff in the setting, including nurses and unregulated care providers. Although the residential aged care setting can be a challenging learning environment for students, it also offers opportunities for student growth and professional development, especially when there are clearly articulated learning outcomes and appropriate role models available.